DEVELOPING MEDIA COMPETENCE IN ENGLISH TEACHING IN PRIMARY GRADES: METHODS AND SUGGESTIONS - Valiyeva Shakhlo Akmalovna (Journals Park Publishing, 2025)
This article examines the issue of integrating media education into the traditional learning process in teaching English in primary grades. The article presents methods aimed at increasing students' media literacy and protecting them from misinformation. The importance of technology and media tools in teaching English is emphasized, as well as the importance of teaching students analytical thinking through interactive lessons and multimedia. The need to develop students' skills in creating media texts, correctly interpreting and analyzing information is emphasized.
Keywords: Components, tendency, media textbook, interactivity, didactic study, primary school, lesson process, animation.